Characterization of mechanical properties of natural fibre reinforced polymer composite using horizontal and vertical kenaf fibre orientation - Isharudden F.M.; Isa M.R.; Zaroog O.S.; Jalal M.F.A.; Sulaiman S.N.; Ismail I.N.; Zahari N.M.; Mohamed H.; Roslan E. (American Institute of Physics Inc., 2023)
Natural fibre composite (NFC) displays a rapid development in the study and innovation sector due to the increasing benefits of the material compared to other types of fibre such as synthetic fibre composites, which includes low price and low environmental impacts. These composites can be explored through various variables and can be tested through various factors such as fibre interfacial adhesion, fibre orientation and fibre strength. However, this thesis focuses only on the testing on the vertical (90) and horizontal (0) of fibre orientation as it is still not well investigated, yet. The main objective of this research is to investigate the performance of mechanical properties of kenaf fibre reinforced epoxy resins for 90 and 0 of fibre orientation and analyse the effect of changing the orientation on the material. For the fabrication of the material, manual preparation method has been used and several mechanical testing has been and alkali treatment of kenaf fibre prior fabrication process. For hardness test, the 90 of fibre orientation produced 31.6% higher of hardness strength than 0 of fibre orientation while for impact test, 90 of fibre orientation resulted 39.5% greater of impact energy than 0 of fibre orientation. 6% of kenaf fibre composition with 90 of fibre orientation generated the highest stress to breaks while 2% of kenaf fibre composition with 0 of fibre orientation has the lowest stress to fracture. By conducting the SEM tests, it can be seen clearly that 6% of kenaf fibre composition with 90 of fibre orientation has the smallest gap between the fibres and 2% of kenaf fibre composition with 0 of fibre orientation has the largest gap between fibres. Thus, the performance of mechanical of vertical (90) of fibre orientation produced better performance in mechanical testing compared to horizontal (0) of fibre orientation. 2021 American Institute of Physics Inc.. All rights reserved.